Eksistensi Pemerintahan Nagari di Sumatera Barat Dalam Kajian Sejarah - Harisnawati harisnawati; Sri Rahayu; Intan Sri Wahyuni (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2018)
Motivated by the birth of various problems that arise related to various regulations that were created by the nagari. As a